2014
DOI: 10.1109/jphotov.2014.2313225
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of High-Efficiency III–V on Silicon Multijunction Solar Cells by Direct Metal Interconnect

Abstract: This paper presents a novel direct-metal-interconnect hybrid integration method for the fabrication of low cost and highefficiency multijunction solar cells without being constrained by lattice matching requirements. It also incorporates the areal current matching technique that is essential in mitigating the adverse effects of current limiting by the Si subcell to achieve maximum possible efficiency. A GaInP/InGaAs/Si triple-junction solar cell has been demonstrated, with a 2-terminal estimated efficiency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 16 publications
1
38
0
Order By: Relevance
“…Si being an indirect bandgap semiconductor typically limits the overall current when integrated in tandem with conventional 2J InGaP/GaAs solar cells in 3J twoterminal configuration (Derendorf et al 2013;Yang et al 2014;Garcia-Tabares et al 2011). Hence, the design of bottom Si subcell is extremely important for current-matching in tandem cell design.…”
Section: Iii-v and Si Solar Cell Design And Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…Si being an indirect bandgap semiconductor typically limits the overall current when integrated in tandem with conventional 2J InGaP/GaAs solar cells in 3J twoterminal configuration (Derendorf et al 2013;Yang et al 2014;Garcia-Tabares et al 2011). Hence, the design of bottom Si subcell is extremely important for current-matching in tandem cell design.…”
Section: Iii-v and Si Solar Cell Design And Challengesmentioning
confidence: 99%
“…DMI technique is capable of providing high tolerance to disparate materials with difference in lattice constants and thermal expansion coefficients, allowing for greater freedom in choosing the subcell materials with optimal bandgap combinations. Yang et al (2014) demonstrated a 3J GaInP/GaAs/Si solar cell using the DMI approach. The 2J GaInP/GaAs cells were first grown on lattice-matched Ge substrate, thereafter the substrate was removed using epitaxial lift-off technique, and the metallized front side of the 2J cell was attached to a transparent quartz wafer for support.…”
Section: Direct Metal Interconnectmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent developments in tandem solar cells and broadband photodetectors have caused an increasing research interest in materials integration between group-IV and III-V semiconductors. 1,2 Monolithic growth of Ge-on-GaAs and/or GaAs-on-Ge has thus been a natural focus for band broadening because of the small lattice mismatch ($0.083%) between Ge and GaAs. Unfortunately, atomic interdiffusions across the grown interface during the overgrowth caused by the 'selfannealing' effect pose a great challenge, 3,4 beside the polar/ nonpolar mismatch problem when growing GaAs-on-Ge, 5 for materials integration of Ge and GaAs by any epitaxial growth method.…”
Section: Introductionmentioning
confidence: 99%
“…And the heteroepitaxial growth of In x Ga 1 − x As films on Si substrates are expected to be used for the fabrication of high-efficiency solar cells [6,7], laser diodes [8,9], photodetectors [10,11], and so on. In particular, the In x Ga 1 − x As with high In composition of 0.53 is a promising candidate III-V compound semiconductor for a metal-oxide-semiconductor field-effect transistor (MOSFET) channel material due to its high electronic mobility and high breakdown field [12,13].…”
Section: Introductionmentioning
confidence: 99%